Beyond the Rim: A Comparative Study of Kava Bowls from Samoa, Tonga and Fiji - Boissonnas, Valentin (Waka Kuaka, 2015)
The article presents a detailed comparative study of kava mixing bowls associated with the cultural complex of the West Polynesian kava-circle and its Fijian yaqona circle offshoot. By cross-referencing archaeological evidence, documented collection histories and bowl typologies a clearer picture emerges of the centres where the bowls were produced and the formal evolution of these vessels, and also illustrates in a unique way how different groups of people and goods moved and were moved around Western Polynesia in the 18th and 19th century.